Index of fatigue quadriceps in soccer athletes after anterior cruciate ligament reconstruction - Maria Luzete Costa Cavalcante; Paulo Renan Lima Teixeira; Tamara Cristina Silva Sousa; Pedro Olavo de Paula Lima; Rodrigo Ribeiro Oliveira (Revista Brasileira de Ortopedia)
ABSTRACT OBJECTIVE: The present study aimed to evaluate the muscle fatigue of the quadriceps muscle in high-performance soccer players undergoing (anterior cruciate ligament) ACL reconstruction. METHODS: We evaluated 17 high-performance soccer players from three professional soccer teams of a state in Brazil from August 2011 to July 2012. All subjects were evaluated between 5.5 and 7 months after ACL reconstruction with a Biodex(r) isokinetic dynamometer (System 4 Pro) with test protocol CON/CON at 60°/s and 300°/s with 5 and 15 repetitions, respectively. In the calculation of local muscle fatigue, the fatigue index was used, which is calculated by dividing the labor done in the first one-third of the repetitions by that done at the final one-third of the repetitions, and multiplying by 100 to express a unit in percentage (i.e., as a discrete quantitative variable). RESULTS: All subjects were male, with a mean age of 21.3 ± 4.4 years and mean BMI 23.4 ± 1.53 cm; left dominance was observed in 47% (n = 8) of athletes, and right dominance, in 53% (n = 9) of athletes; and the limb involved in the lesion was the dominant in 29% (n = 5) and the non-dominant in 71% (n = 12). Fatigue rates were 19.6% in the involved limb and 29.0% in the non-involved limb. CONCLUSION: The results allow us to conclude that there was no significant difference between the limbs involved and not in ACL injuries regarding local muscle fatigue. No association was observed between the dominant side and the limb involved in the ACL injury.